Inhibition of Gasdermin D-Mediated Pyroptosis Attenuates the Severity of Seizures and Astroglial Damage in Kainic Acid-Induced Epileptic Mice - Xia, Lu; Liu, Lu; Cai, Yiying; Zhang, Yiying; Tong, Fangchao; Wang, Qiang; Ding, Jing; Wang, Xin (Frontiers in Pharmacology, 2022)
Objective: Our study aimed to explore whether gasdermin D (GSDMD)-mediated pyroptosis is involved in the mechanism of kainic acid-induced seizures. Methods: C57BL/6 mice were randomly divided into sham and epilepsy groups. The epilepsy group was intrahippocampally injected with kainic acid to induce status epilepticus (SE), and the sham group was injected with an equal volume of saline. Dimethyl fumarate (DMF) was used as the GSDMD N-terminal fragments (GSDMD-N) inhibitor and suspended in 5% sodium carboxymethyl cellulose (CMC) for orally administration. The epilepsy group was divided into SE+ CMC and SE+ DMF groups. In the SE+DMF group, DMF was orally administered for one week before SE induction and was continued until the end of the experiment. An equal volume of CMC was administered to the sham and SE+CMC groups. Recurrent spontaneous seizures (SRSs) were monitored for 21 days after SE. Western blot analysis and immunofluorescent staining was performed. Results: The expression of GSDMD increased at 7 days and 21 days post-SE, and GSDMD-N expression was significantly evaluated 7 days after SE in both ipsilateral and contralateral hippocampus. GSDMD-positive cells were co-labeled with astrocytes, but not neurons or microglia. Astroglial damage occurs following status epilepticus (SE). Damaged astrocytes showed typical clasmatodendrosis in the CA1 region containing strong GSDMD expression at 7 and 21 days post-SE, accompanied by activated microglia. In the SE+DMF group, the expression of GSDMD-N was significantly inhibited compared to that in the SE+CMC group. After administration of DMF, SRSs at 7–21 days after SE were significantly decreased, and the number of clasmatodendritic astrocytes, microglia, and the expression of inflammatory factors such as IL-1β and IL-18 were significantly attenuated. Conclusions: GSDMD-mediated pyroptosis is involved in the mechanism of kainic acid-induced seizures. Our study provides a new potential therapeutic target for seizure control.